Pengaruh Kualitas Layanan Inti dan Kualitas Layanan Encounter terhadap Niat Beralih: Sebuah Peran Mediasi Kepuasan Pelanggan (Studi pada pengunjung Hotel Fitra dan Hotel Garden Majalengka) - Alan Rusdiana; L Suparto (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
This research is a development of previous research. In this study, customer satisfaction is divided into two, namely transaction-based satisfaction and overall satisfaction. This type of research is associative research. This research takes the title: